Lowering Red Meat and Processed Meat Consumption With Environmental, Animal Welfare, and Health Arguments in Italy: An Online Experiment - Dijkstra, Arie; Rotelli, Valentina (Frontiers in Psychology, 2022)
Introduction In addition to being a source of valuable nutrients, meat consumption has several negative consequences; for the environment, for animal welfare, and for human health. To persuade people to lower their meat consumption, it is assumed that the personal relevance of the topic of lowering meat consumption is important as it determines how people perceive the quality of the arguments. Method In an experimental exploratory field study (n = 139), participants recruited from the general Italian population were randomized to one of the four conditions with a text with pictures on the environmental, animal welfare, or health consequences of meat consumption, or a text on mustard (the control condition). The dependent variables were self-reported consumption of red meat and processed meat after 2 weeks. Personal relevance was assessed in the pre-test with self-reported meat consumption and intention. Results The interaction between pre-test meat consumption and condition was significant: In participants who scored high on pre-test meat consumption, the self-reported red meat consumption after 2 weeks in the health argument condition was significantly lower compared to the control condition and the environmental argument condition. The effects of pre-test intention as a moderator were less certain. Discussion The persuasive effects of the different arguments made a difference only in people who ate a relatively high level of meat in pre-test, and the type of arguments made a difference. Although the present outcomes are caused by the specific formulations of the arguments in this study, the results do show that it is relevant to choose the arguments carefully to ensure effectiveness.